HUBUNGAN ANTARA PARITAS DAN RIWAYAT ABORTUS DENGAN KEJADIAN ABORTUS DI RSUD Prof. Dr. MARGONO SOEKARJO PURWOKERTO TAHUN 2007 - Nurhidayati Nurhidayati; Tin Utami (Universitas Harapan Bangsa Purwokerto, 2009)
Background : The causes of maternal mortality is greatest bleeding (42%), one of which isabortion (11%) (MOH, 2006). More than 80% of abortions occur in the first 12 weeks ofpregnancy, spontaneous bortus risikoa incidence increasing with increasing parity of 12% to26%. Pre survey conducted in hospitals Prof. Dr. Margono Soekarjo Purwokerto, in 2013 asmany as 327 (15.06%) out of 2171 pregnant women. This shows an increase in abortion figuresfrom the year 2006 to year 2007 by 6 cases (0.2%) of pregnant women. Objective : The aim of this study was to determine is there a relationship between parity andhistory of abortion by abortion in hospitals Prof. Dr. Margono Soekarjo Purwokerto in 2013. Methods : The method used is the analytic survey with case control design, this study usessecondary data was acquired on 2, 3,7, 8, 9, 10, and July 21, making use of purposive samplingtechniques, sample of 96 respondents Results : There is a significant relationship between parity with the incidence of abortion, this isevidenced by the p value (0.0001) <Î± (0.05). There is a significant association between a historyof abortion by abortion, this is evidenced by the p value (0.0001) <Î± (0.05). Keywords : parity, history of abortion, abortion.